Prognostic Significance of Cyclin E1 Expression in Patients With Chordoma: A Clinicopathological and Immunohistochemical Study - Wei, Ran; Dean, Dylan C.; Thanindratarn, Pichaya; Hornicek, Francis J.; Guo, Wei; Duan, Zhenfeng (Frontiers in Oncology, 2020)
Purpose Chordomas are rare, slow-growing sarcomas without any accepted prognostic biomarkers. Owing to their proximity to critical neurovascular structures, discovering predictive biomarkers in chordoma has been a significant research effort because it may potentially reduce risky therapies in patients with less aggressive tumors. In response, because cyclin E1 overexpression correlates with patient prognosis in several malignancies, we investigated its expression in chordoma and whether it informs patient prognosis. Methods Seventy-five chordoma patient specimens were enrolled in a tissue microarray (TMA) to evaluate cyclin E1 expression via immunohistochemical staining. Western blot was used to assess cyclin E1 expression in chordoma cell lines and fresh tissues. We then correlated cyclin E1 staining intensity in the TMA to clinicopathological features and chordoma patient outcomes. Results Sixty-three percent of the chordoma patient specimens in the TMA, fifty-six percent of the fresh chordoma tissues, and all chordoma cell lines showed high cyclin E1 expression. In TMA analysis, cyclin E1 expression positively correlated to chordoma patient disease status. By survival analysis, high cyclin E1 expression was an independent prognostic risk factor for chordoma patients along with advanced disease status and positive surgical margin. Conclusion Cyclin E1 is a promising biomarker predicting chordoma patient prognosis.